Basolateral amygdala volume in affective disorders using 7T MRI in vivo - Benedikt Kürzinger; Stephanie Schindler; Martin Meffert; Anja Rosenhahn; Robert Trampel; Robert Turner; Peter Schoenknecht; Peter Schoenknecht; Peter Schoenknecht (Frontiers in Psychiatry)
BackgroundThe basolateral complex of the amygdala is a crucial neurobiological site for Pavlovian conditioning. Investigations into volumetric alterations of the basolateral amygdala in individuals with major depressive disorder (MDD) have yielded conflicting results. These may be reconciled in an inverted U-shape allostatic growth trajectory. This hypothesized trajectory unfolds with an initial phase of volumetric expansion, driven by enhanced dendritic arborization and synaptic plasticity. The increase in volume is followed by a reduction phase, as glucocorticoid exposure cumulatively results in excitotoxic damage, reflecting allostatic load.Methods7T magnetic resonance brain imaging was conducted on a total of 84 participants (mean age 38 ± 12 years), comprising 20 unmedicated and 20 medicated individuals with MDD, 21 individuals suffering from bipolar disorder and 23 healthy controls. We employed FreeSurfer 7.3.2 for automatic high-resolution segmentation of nine amygdala subnuclei. We conducted analyses of covariance, with volumes of the basolateral complex, the lateral nucleus and, exploratively, the whole amygdala, as dependent variables, while controlling for the total intracranial volume and sex. Quadratic regressions were computed within the MDD group and in relevant subgroups to investigate the presence of a U-shaped relationship between the number of preceding major depressive episodes or the duration of the disease since the first episode and the dependent variables.ResultsDiagnostic groups did not exhibit statistically significant differences in the volumes of the basolateral amygdala (left F (3,75) = 0.66, p >.05; right F (3,76) = 1.80, p >.05), the lateral nucleus (left F (3,75) = 1.22, p >.05; right F (3,76) = 2.30, p >.05)), or the whole amygdala (left F (3,75) = 0.48, p >.05; right F (3,76) = 1.58, p >.05). No quadratic associations were observed between surrogate parameters of disease progression and any of the examined amygdala volumes. There were no significant correlations between subregion volumes and clinical characteristics.ConclusionWe found no evidence for the hypothesis of an inverted U-shaped volumetric trajectory of the basolateral amygdala in MDD. Future research with larger sample sizes, including the measurement of genetic and epigenetic markers, will hopefully further elucidate this compelling paradigm.